2009
DOI: 10.1063/1.3115826
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of subthreshold current transport by contact interface modification in p-type organic field-effect transistors

Abstract: The charge injection efficiency of organic field-effect transistors (OFETs) is found to be a critical factor determining the subthreshold characteristics of these devices. OFETs fabricated using a wide band gap organic semiconductor and gold source/drain contacts display large threshold voltage and poor subthreshold characteristics. Insertion of a metal-oxide charge injection layer at the contact/semiconductor interface lower the injection barrier height, resulting in marked improvements in threshold voltage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 16 publications
4
132
0
Order By: Relevance
“…[ 100 ] A similar effect of the contact resistance between the semiconductor and the electrode was observed for vapor-deposited 33b - [ 60b ]…”
Section: Fet Characteristics and Solid-state Packing Structuressupporting
confidence: 60%
“…[ 100 ] A similar effect of the contact resistance between the semiconductor and the electrode was observed for vapor-deposited 33b - [ 60b ]…”
Section: Fet Characteristics and Solid-state Packing Structuressupporting
confidence: 60%
“…36 The transistor electrodes doped by TMOs can markedly increase the μ FET and lower the threshold voltage. [37][38][39] It was also reported that aqueous TMO solutions can be used for the doping process in solution-processed devices. 40,41 As shown in Figure 5a and Supplementary Figure S10, the hydrophilic source/drain electrodes on the hydrophobic substrate, combined with the Cytop guide layer, efficiently guide the spontaneous location of aqueous dopant solutions for the precise deposition of dopants.…”
Section: Resultsmentioning
confidence: 99%
“…Various research groups focus on materials such as dinaphtho(2,3-b:2′,3′-f)thieno (3,2-b)thiophene (Cn-DNTT) and 2,7-dioctyl(1)benzothieno(3,2-b)(1)benzothiophene (C8-BTBT), which can be deposit by thermal evaporation or from solutions, respectively [13][14][15][16]. Currently, the highest achieved field-effect mobility is about 43 cm 2 /Vs for C8-BTBT deposited by a special off-centered spin-coating technique [17].…”
Section: Integrationmentioning
confidence: 99%